Social responsibility in Miraflores restaurants, Lima - Horna Bances, Esteban Vicente (2018)
To stablish the main strengths and weaknesses of the company with the aim of building a clear vision of its current situation, from the perspective of the Chief Executive officers and managers of restaurants located in the district of Miraflores, Lima- Peru a survey was performed during july and august 2015.80 persons were interviewed and the results showed mainly that almost always they had actions to improve the quality of life, and of commitment with society, the environment and the stakeholders. In addition, significant relationship between quality of life and the commitment with environment and stakeholders but not with stakeholders.On the other hand, there is independence between commitment with society and environment and commitment with stakeholders